Overlapping genres, as portrayed in Marie Ndiaye's Autroportrait en vert (Green self-portrait) - Polverel, Elsa (Sens public)

(untitled) (Département des littératures de langue française, 2009)
« It’s the evening and the Garonne River is rising hour after hour in the darkness ». Page after page, the water penetrates the text and the walls; the banks become porous, permeable. Identities blend and confusion invades the text, the narrator and the reader…“You have to watch and wait”. Along with the rising waters, the narrator’s encounters with the women in green increase in timelessness, and exist as incarnations of the flooding Garonne. Autoportrait en vert (Green self portrait) by Mary Ndiaye is a work which, through its structure and writing, challenges the notions of literary, photographic, identity and normative genres by jeopardising and questioning our own representations of the world.